Análisis del endeudamiento interno del Ecuador como consecuencia de las variaciones del precio del barril del petróleo, periodo 2010-2017 - Bustos Roble, Nadia Cristina (2019)
The purpose of this research is to analyze the internal indebtedness of the Ecuadorian economy and the variations in the price of a barrel of oil in the 2010-2017 periods. For this purpose, reference is made as references to economic theories, techniques, methods and research procedures that they will allow us to determine if the internal indebtedness is correlated with the constant fluctuations of the price of a barrel of oil and that this relationship has such an impact on the economy of the country. The work will have a historical-descriptive analysis of the domestic public debt balances as well as fluctuations in the price of a barrel of oil, starting from the first oil boom in the 70s in order to be able to make comparisons of the different periods until the study period, this allows us to perform an analysis and compare the data and thus determine if there is a correlation between the study variables………..